Fournier's gangrene reconstruction: A 10-year retrospective analysis of practice at Guys and St Thomas's NHS Foundation Trust. (May 2023) - Biju, Noel E.; Sadiq, Muhayman; Raj, Siddarth; Patel, Aman; Shah, Rushabh; Weale, Ross David; Thomas, Kay; Rose, Victoria
Summary: Fournier's gangrene is a rare and potentially fatal condition that affects the external genitalia and perineum as a necrotizing soft-tissue infection. It is equally prevalent in men and women and although there are many ways to manage the condition, it must be done so effectively because there is a chance that life-threatening complications could develop. This retrospective study set out to fill any knowledge gaps, compare reconstructive options to those described in the literature, and promote reflection on current management. Between January 2010 and January 2020, all perineal debridement operation notes were examined. The primary conclusions were that a large majority of defects could be repaired using split skin grafts to reduce surgical time and donor site morbidity. To avoid secondary contracture and the need for revision surgery, full-thickness skin grafts should be used whenever possible to treat penile defects.